2017
DOI: 10.1186/s13287-017-0743-7
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-derived stem cells ameliorate hyperglycemia, insulin resistance and liver fibrosis in the type 2 diabetic rats

Abstract: BackgroundType 2 diabetes (T2D) is closely associated with liver fibrosis, but no effective treatments are currently available. This study was designed to investigate the therapeutic effects of ADSCs on insulin resistance, hyperglycemia, and liver fibrosis on T2D rats.MethodsWe first established a T2D rat model with liver fibrosis by using the combination of a high-fat diet (HFD), low-dose streptozotocin (STZ), and carbon tetrachloride (CCl4). Subsequently, the model rats were administrated by tail vein inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 34 publications
4
40
0
Order By: Relevance
“…Isolation of ADSCs was performed according to our previous reports [2][3][4]. Brie y, subcutaneous fat tissues were collected from the groin area of male C57BL/6 mice (n=10), and then cut into about 0.1mm 3 size and digested with 0.1% type I collagenase (Sigma-Aldrich, USA) in HBSS (Hyclone, USA) at 37 °C for 1 h. Afterwards, the digestive solutions were neutralized by α-MEM (Hyclone, USA) containing 20%FBS (Gibco, USA), ltered through a 100-μm cell strainer, followed by eliminating the red blood cells with osmotic lysates (Biyuntian Biological Co., Ltd., Shanghai, China).…”
Section: Isolation and Culture Of Adscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation of ADSCs was performed according to our previous reports [2][3][4]. Brie y, subcutaneous fat tissues were collected from the groin area of male C57BL/6 mice (n=10), and then cut into about 0.1mm 3 size and digested with 0.1% type I collagenase (Sigma-Aldrich, USA) in HBSS (Hyclone, USA) at 37 °C for 1 h. Afterwards, the digestive solutions were neutralized by α-MEM (Hyclone, USA) containing 20%FBS (Gibco, USA), ltered through a 100-μm cell strainer, followed by eliminating the red blood cells with osmotic lysates (Biyuntian Biological Co., Ltd., Shanghai, China).…”
Section: Isolation and Culture Of Adscsmentioning
confidence: 99%
“…Author details 1 The United Innovation of Mengchao Hepatobiliary Technology Key Laboratory of Fujian Province, Mengchao Hepatobiliary Hospital of Fujian Medical University; 2 Liver Disease Center, The First A liated Hospital of Fujian Medical University; 3 Mengchao Med-X Center, Fuzhou University; 4 The Liver Center of Fujian Province, Fujian Medical University.…”
Section: Availability Of Supporting Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Regenerative medicine using adipose tissue-derived mesenchymal stem cell (ADSC) transplantation provides a promising alternative strategy for chronic liver disease treatment by using the intrinsic abilities of ADSCs including multilineage differentiation potential, self-renewal, and immunomodulation properties. In particular, ADSC transplantation has been widely used for treating liver fibrosis [2], non-alcoholic liver diseases [1,[3][4][5], and cirrhosis [6] in the preclinical studies, but the long-term therapeutic outcomes are very poor and far from satisfaction, due to the extremely low hepatic engraftment efficiency of ADSCs. In most cases, the hepatic retention of stem cells is less than 5% after cell infusion for 4 weeks [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BAT is an important endocrine organ that secretes a variety of adipokines [12] and miRNAs [13] involved in systemic metabolic regulation, and the latter are involved in the regulation of a variety of biological processes and metabolic homoeostasis, including lipid metabolism, inflammation, oxidative stress, etc. Recent studies have found that transplantation of adipose tissue-derived stem cells (ADSCs) can significantly improve NAFLD and related liver fibrosis and cirrhosis in the rat or mouse model [14][15][16][17]. And the study has shown that BAT transplantation can improve glucose tolerance, increased insulin sensitivity, lower body weight, decreased fat mass and a complete reversal of high-fat diet (HFD)-induced insulin resistance in mice [18].…”
Section: Introductionmentioning
confidence: 99%